Furman at 45: Constitutional Challenges from California's Failure to (Again) Narrow Death Eligibility. Issue 4 (22nd November 2019) - Baldus, David C.; Woodworth, George; Grosso, Catherine M.; Laurence, Michael; Fagan, Jeffrey A.; Newell, Richard
Abstract : The Eighth Amendment's "narrowing" requirement for capital punishment eligibility has challenged states since it was recognized in Furman v. Georgia in 1972. This article examines whether California's death penalty scheme complies with this requirement by empirically analyzing 27, 453 California convictions for first‐degree murder, second‐degree murder, and voluntary manslaughter with offense dates between January 1978 and June 2002. Using a 1, 900‐case sample, we examine whether California's death penalty statute fails to comply with the Eighth Amendment's narrowing test. Our findings support two conclusions. First, the death‐eligibility rate among California homicide cases is the highest in the nation during that period and in the ensuing decade. We find that 95 percent of all first‐degree murder convictions and 59 percent of all second‐degree murder and voluntary manslaughter convictions were death eligible under California's 2008 statute. Second, a death sentence is imposed in only a small fraction of the death‐eligible cases. The California death sentencing rate of 4.3 percent among all death‐eligible cases is among the lowest in the nation and over two‐thirds lower than the death‐sentencing rate in pre‐ Furman Georgia.